STUDY OF THE DEVELOPMENT OF WASTEWATER TREATMENT SYSTEMS AND THE YUAN ISLAND AS A TOURIST ATTRACTION OF NAKHON SAWAN MUNICIPALITY'S YUAN CHUAN RAK CANAL FOR DEVELOPING A GEOGRAPHICAL DATABASE AND PROGRAMED INSTRUCTION - Dinfa, Patcharee (Journal of MCU Nakhondhat, 2023)
The purposes of this research were: to study on the development of wastewater treatment system and Yuan Island as a tourist attraction of Nakhon Sawan Municipality's Yuan Chuan Rak Canal, Create a spatial database to promote tourism of Nakhon Sawan Municipality's Yuan Chuan Rak Canal, and to create of the programed instruction of Environment and Population Studies Subject. How to conduct research this research was the qualitative research. The main informants of the research objectives were 30 people ; government, local and people. The place of study was Koh Yuan community, Nakhon Sawan. Use a semi - structured Interview form, and data were analyzed by descriptive. The findings of this research as following : The way of life of the people in the Yuan Island community improved quality of life after Nakhon Sawan Municipality developed a wastewater treatment system and Yuan Island as a tourist attraction.Promote sustainable local economy creating jobs, creating careers, and distributing income from tourism to the people of the island of Yuan. The infrastructure/utilities have been improved. a place to rest Walking for exercise or cycling promote good health There is an exchange of knowledge between government agencies. local sector and people It is to encourage people to be conscious of preserving the locality and the water environment. Participate in the maintenance of the tourist attraction Khlong Yuan Chuan Rak and is a source of learning Study tour on water resource conservation and sustainable water management for educational institutions Government and private agencies Both in Nakhon Sawan and other provinces. The spatial database for promoting tourism of the Nakhon Sawan Municipality's Yuan Chuan Rak Canal and ready - made lessons in the subject of environment and population studies have been published on the website. https://hss.nsru.ac.th/knowledge/patcharee.d/of Humanities and Social Sciences Nakhon Sawan Rajabhat University.